Bulletin 80 A Primer on Explosives for Metal Miners and Quarrymen - Charles E. Munroe; Clarence Hall (The National Institute for Occupational Safety and Health (NIOSH), 1915)
In accidents resulting from the use of explosives in metal mines and quarries in the United States more than 130 men were killed and 250 seriously injured during the calendar year 1913. More- over, an unknown number of miners suffered from the effects of breathing the harmful fumes and gases given off by the burning or the incomplete explosion of some explosive. Consequently, the Fed- eral Bureau of Mines, which is endeavoring to increase safety in mines and to abolish conditions that tend to impair the health of miners, is studying the kinds of explosives used in mining and the conditions under which these explosives can be used with least danger to the miner. Information about the different explosives used in coal mining and the precautions to be taken in using those explosives has been printed in Bulletin 17 and other bureau reports, the names of which may be found at the end of this bulletin. The bureau has not been able to give much attention to explosives used in metal mines and quarries, but has published some information about these explosives in Bulletin 48, "The Selection of Explosives Used in Engineering and Mining Operations"; Technical Paper 17, "The Effect of Stemming on the Efficiency of Explosives"; and Miners' Circular 19, "The Prevention of Accidents from Explosives in Metal Mining." This bulletin aims to give the metal miner and the quarryman information similar to that given the coal miner in Bulletin 17. In- flammable gas or dust is seldom, if ever, found in quarries or metal mines, and the danger from using explosives there is less than in coal mines; but, as the figures show, the number of men killed and injured yearly in accidents caused by explosives proves the need of both miners and mine officials striving to see that none but proper explosives are used and that these are used properly.